Doctor–patient communication in rural Indonesia: a pragmatic study of directive speech acts in clinical consultations - Iin Linda Nazulpa (Indonesian Journal of Medical Linguistics, 2026)
Background: Rural healthcare communication in Indonesia presents complex interactional challenges where institutional authority intersects with sociocultural norms of politeness and hierarchy. Objective: This study aims to examine how directive speech acts are produced, mitigated, and sequentially organized in rural clinical consultations. Method: Using a qualitative pragmatic design, 42 recorded consultations (864 directive tokens) from community health centers, private clinics, and mobile services were transcribed and analyzed through Speech Act Theory, Politeness Theory, and Conversation Analysis. Results: The results show that advice (44.0%) and instruction (28.7%) dominate over direct commands (8.5%), indicating preference for mitigated authority. Negative politeness strategies account for 65.3% of directives, with modal verbs and hedges as primary mitigation devices. Sequential analysis reveals that short pauses correlate with immediate acknowledgment, whereas longer pauses significantly predict repair sequences. Implication: This study demonstrates that medical authority in rural Indonesia is enacted through calibrated mitigation and interactional sensitivity rather than overt coercion. Novelty: The novelty lies in integrating illocutionary classification, face management analysis, and sequential metrics into a unified model of directive negotiation in non-Western clinical discourse.